Identification of vulnerable areas in Bago City using the drastic approach and simulation of lead transport in the underlying aquifer using ASMWIN - Pandan, Mary Ann Torres (2000)
The DRASTIC system which is an assessment method based on the hydrogeological setting was used to determine the relative vulnerability to groundwater contamination in Baguio City. Seven parameters, namely (1) D - depth to groundwater (2) R - recharge rate (3) A - aquifer media (4) S - soil media (5) T - topography (slope) (6) I - impact of the vadose zone and (7) C - conductivity (hydraulic) of the aquifer were used to assess the potential for contamination in the study area. Highly vulnerable areas were identified in the coastal areas while the least vulnerable areas were in the mountainous regions. Using the DRASTIC index, possible sources of contamination were evaluated. The one which presents the greatest risk was established and this is the open dumpsite. For this type of source, the threat of leachate infiltration was considered and its annual volume was calculated at 27320 cu.m. The heavy metals in the leachate were of major concern specifically, lead (Pb) and based on monitoring data from a similar disposal site, its concentration was assumed to be 0.397 mg/L.